2000
DOI: 10.1007/s101100050040
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of new firm success

Abstract: The differences between new firms, even the differences present right at the start, may affect their life course and success over time. This article addresses the determinants of success of Dutch start-ups from a longitudinal perspective. After an overview of the literature on both the definition of success and the success factors of new firms we test how new firm characteristics relate to firm growth in number of employees using a panel of nearly 2,000 firms. In addition to a large firm size right from the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 12 publications
7
68
0
8
Order By: Relevance
“…The legal type of business is not a significant factor in explaining small firm growth in different sectors and for different sizes (H 3 not supported). Findings partially support (only for manufacturing firms, H 7 partially supported), previous research suggesting that firms funded by an entrepreneurial team are more likely to grow faster in comparison to those funded by an individual (Schutjens and Wever 2000). One possible explanation for this finding is that manufacturing firms benefit from engaging in rather larger investment projects needing large funds which are made possible by a larger group of investors, compared to their counterparts in the services and trade.…”
Section: Institutional Factorssupporting
confidence: 77%
See 1 more Smart Citation
“…The legal type of business is not a significant factor in explaining small firm growth in different sectors and for different sizes (H 3 not supported). Findings partially support (only for manufacturing firms, H 7 partially supported), previous research suggesting that firms funded by an entrepreneurial team are more likely to grow faster in comparison to those funded by an individual (Schutjens and Wever 2000). One possible explanation for this finding is that manufacturing firms benefit from engaging in rather larger investment projects needing large funds which are made possible by a larger group of investors, compared to their counterparts in the services and trade.…”
Section: Institutional Factorssupporting
confidence: 77%
“…The synergy effects of the knowledge of founders, especially in teams with those members who have complementary skills (Corbett 2007). The synergy effect expands knowledge, increases managerial capabilities and in addition to the knowledge synergy the partners may act as a signalling for potential creditors and lenders of the seriousness and economic strength of the business leading to higher growth (Schutjens and Wever 2000;Pasanen and Laukkanen 2006). Thus, the following hypothesis states: H 7 : Growth is positively associated with the entrepreneurial teams…”
Section: Human Capitalmentioning
confidence: 94%
“…However, evidence is not conclusive with regard to the effect of firm location on growth (Almus & Nerlinger, 1999;Brixy & Kohaut, 1999;McPherson, 1996;Schutjens & Wever, 2000;Storey, 1994). Furthermore, Hoogstra and van Dijk (2004) found that the effect of location differs by the type of economic activity.…”
Section: Literature Reviewmentioning
confidence: 89%
“…The presence of an entrepreneurial team has also been shown to have a positive influence on growth. Evidence suggests that new ventures founded by a team are more likely to grow faster than those founded by an individual (Almus & Nerlinger, 1999;Schutjens & Wever, 2000;Storey, 1994).…”
Section: Literature Reviewmentioning
confidence: 97%
“…The explanation for this positive relationship is twofold. First, there are factors inherent in newly established enterprises that limit their average life expectation (Schutjens and Wever 2000), and lead to the 'revolving door' regime described by Audretsch and Fritsch (1992). Second, newly founded companies compete with existing firms and force them to adapt or even to close, although closures of established enterprises are less frequent than the displacement of young firms by new ones.…”
Section: Introductionmentioning
confidence: 99%